Irradiation delays tissue growth but enhances osteogenic differentiation in vascularized constructs - Eweida, Ahmad; Rosenbauer, Olga; Frisch, Oliver; Giordano, Frank Anton; Fleckenstein, Jens; Wenz, Frederik; Kirschner, Stefanie; Brockmann, Marc Alexander; Schulte, Matthias; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of reconstructive microsurgery, 2019)
Background: Regenerative medicine is still deficient in the reconstruction after cancer due to impaired vascularization after radiotherapy and due to the need to substitute larger defects after tumor excision. Aiming at introducing regenerative medicine for reconstruction after cancer, we tested an axially vascularized bone construct in an experimental setting that mimics the clinical situation after tumor resection and adjuvant radiotherapy. Methods: Twenty bone constructs were axially vascularized using microsurgically created arteriovenous loops and were implanted subcutaneously in Lewis rats. After 2 weeks, the animals were randomly allocated either to receive a clinically relevant single dose of external beam irradiation or not (n = 10 for each group). The animals were sacrificed either after 1 week or 10 weeks after irradiation (n = 5 for each time point). The constructs were tested for vascularization, tissue growth, cellular proliferation, cellular apoptosis, and osteogenic differentiation via histomorphometric, immunohistochemical, and polymerase chain reaction (PCR) analysis. One construct per group was subjected at 10 weeks to qualitative micro-computed tomography (CT) imaging. Results: Tissue generation and cellular proliferation were significantly reduced at 1 week after irradiation, but no longer significantly different after 10 weeks. No significant differences in vascularization were detected at any time point. Apoptosis did not show any statistically significant differences between both groups at both time points. At the late time point, mature bone was considerably more in the irradiated group, but the results were not statistically significant. PCR analysis showed a significantly enhanced expression of osteocalcin in the irradiated group at 1 week. Micro-CT imaging showed that both constructs were adequately vascularized with no evident morphologic differences regarding vascular density or vascular distribution. Conclusions: Axially vascularized bone constructs can withstand clinically relevant doses of irradiation and retain their angiogenic and osteogenic potential in the long term. Irradiation led to a delayed tissue generation with a comparatively enhanced osteogenic differentiation within the constructs.